Observations at the CNS–PNS Border of Ventral Roots Connected to a Neuroma - Remahl, Sten; Angeria, Maria; Nilsson Remahl, Ingela; Carlstedt, Thomas; Risling, Marten (Frontiers in Neurology, 2010)
Previous studies have shown that numerous sprouts originating from a neuroma, after nerve injury in neonatal animals, can invade spinal nerve roots. In this study the border between the central and peripheral nervous system (CNS-PNS border) of ventral roots in kittens was examined with both light and electron microscopy after early postnatal sciatic nerve resection. A transient ingrowth of substance P positive axons was observed into the CNS, but no spouts remained 6 weeks after the injury. Using serial sections and electron microscopy it was possible to identify small bundles of unmyelinated axons that penetrated from the root fascicles for a short distance into the CNS. These axons ended blindly, sometimes with a growth cone-like terminal swelling filled with vesicles. The axon bundles were accompanied by p75 positive cells in both the root fascicles and the pia mater, but not in the CNS. It may thus be suggested that neurotrophin presenting p75 positive cells could facilitate axonal growth into the pia mater and that the lack of such cells in the CNS compartment might contribute to the failure of growth into the CNS. A maldevelopment of myelin sheaths at the CNS-PNS border of motor axons was observed and it seems possible that this could have consequences for the propagation of action potential across this region after neonatal nerve injury.